Critical Thinking and the Impact on University Education for Sustainable Development - Chaname-Chira, Ricardo; Santisteban-Chevez, Dyanne; Tafur, Kelly Maricela Reynoso; Villalobos, Peter Garcia; Campos-Ugaz, Walter; Alcaide-Aranda, Lourdes Ivonne Del Carmen; Villegas, Dante Rafael Aguinaga (Indian Journal of Information Sources and Services, 2024)
Man by nature is a homo pensantis. This means that he has the capacity to analyze, synthesize, deduce, etc. However, we must question how educational institutions strengthen critical thinking (CP). Therefore, the purpose of this study was to analyze its level in academic tasks assigned in the classroom context based on active methodologies as an integral element of a quality and sustainable education. The methodology was based on a documentary review with a qualitative and bibliometric approach. The corpus consisted of thirty-one articles extracted from the Scopus database. Likewise, the Prisma Technique was used for the exclusion and inclusion of the documents consulted. The writings are from the years 2020 to 2023. The results showed that CP is a limitation for the student, since its exercise demands the use of complex cognitive skills such as analysis, interpretation, inference, evaluation, etc. It was concluded that PC is necessary in the classroom context, since it is important to induce the search for contradictions and assumptions and to question a reasoning accepted as truth, becoming an indispensable requirement for higher education to provide training tools to students to respond to current sustainable needs.